Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/mc.22045
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐dependent mRNA expression pattern of splicing factor YT521 and its impact on oncological important target gene expression

Abstract: The ubiquitously expressed splicing factor YT521 (YTHDC1) is characterized by alternatively spliced isoforms with regulatory impact on cancer-associated gene expression. Our recent findings account for the prognostic significance of YT521 in endometrial cancer. In this study, we investigated the hypoxia-dependency of YT521 expression as well as its differential isoform activities on oncological important target genes. YT521's potential regulatory influence on splicing was investigated by a minigene assay for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…We hypothesize that perturbation of the regulation by YTHDC1 of potentially oncogenic genes such as RET, PRMT2, RARG and HOXA9 could be involved in the pathogenesis of related tumors. In fact, experimental studies support the implications for YTHDC1 in cancer progression with regard to angiogenesis, growth factor signaling, immortalization, genetic instability, tissue invasion and apoptosis [59,64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that perturbation of the regulation by YTHDC1 of potentially oncogenic genes such as RET, PRMT2, RARG and HOXA9 could be involved in the pathogenesis of related tumors. In fact, experimental studies support the implications for YTHDC1 in cancer progression with regard to angiogenesis, growth factor signaling, immortalization, genetic instability, tissue invasion and apoptosis [59,64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…Exposure of breast cancer cells to hypoxia also leads to the upregulation of ZNF217, a transcription factor known to interact with METTL3 and inhibit its function [77] (Figure 2D). In gynecological tumor cell lines, hypoxia leads to a reduction of YTHDC1 protein levels, through changes in splicing that generate mRNA isoforms targeted by nonsense-mediated decay [78]. The m 6 A reader YTHDC2 [79] has been shown to promote translation of HIF-1 α and contributes to colon tumor metastasis [80].…”
Section: M6a and Cancermentioning
confidence: 99%
“…Previous studies have demonstrated YT521 as an important RNA splicing-related protein, and CD44 is one of the identified targets for YT521. Nevertheless, the biological [18,19]. However, whether YT521 may similarly regulate the splicing of VEGF-A in EC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies were anti-VEGF-A, anti-α-tubulin (R&D System, Los Angeles, CA, USA), and anti-YT521 [18,19]. α-Tubulin was used as a protein loading control for analyzing YT521 levels.…”
Section: Immunoblotmentioning
confidence: 99%
See 1 more Smart Citation